Prevalence of obesity-associated complications in breast cancer women: an integrative review (Research, Society and Development, 2023)
This study aimed to review the literature on how the development of obesity has symptoms and complications in women with breast cancer. It is a literature integrative review that researches in databases BVS, PubMed, and CAPES periodical. It was found that 13 articles related to the subject, furthermore, all the inclusion criterion was checked. This study points out that obese breast cancer women have a higher probability to have peripheral neuropathy, cardiovascular risk, and lymphedema than non-obese women. Likewise, those women have a high chance to present fatigue rates, metabolic changes, and lower quality of life, whereas, practicing fiscal exercise and having good food habits help to prevent those illnesses. So, there is a close association between obesity and more complications, doing fiscal exercise post-treatment and healthy food habits helps to less recurrence of these symptoms. It is important to be specific behavior that prevents complications and gives comfort and quality of life to those patients.